Epidemiological Survey of Dyslipidemia in Civil Aviators in China from 2006 to 2011 - Rongfu Zhao; Dan Xiao; Xiaoying Fan; Zesong Ge; Linsheng Wang; Tiecheng Yan; Jianzhi Wang; Qixin Wei; Yan Zhao (International Journal of Endocrinology)
Aim. This study aimed to analyze blood lipid levels, temporal trend, and age distribution of dyslipidemia in civil aviators in China. Methods. The 305 Chinese aviators were selected randomly and followed up from 2006 to 2011. Their total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels were evaluated annually. Mean values for each parameter by year were compared using a linear mixed-effects model. The temporal trend of borderline high, high, and low status for each index and of overall borderline high, hyperlipidemia, and dyslipidemia by year was tested using a generalized linear mixed model. Results. The aviators' TC (F=4.33, P<0.01), HDL-C (F=23.25, P<0.01), and LDL-C (F=6.13, P<0.01) values differed across years. The prevalence of dyslipidemia (F=5.53, P<0.01), borderline high (F=6.52, P<0.01), and hyperlipidemia (F=3.90, P<0.01) also differed across years. The prevalence rates for hyperlipidemia and dyslipidemia were the highest in the 41–50-year-old and 31–40-year-old groups. Conclusions. Civil aviators in China were in high dyslipidemia and borderline high level and presented with dyslipidemia younger than other Chinese populations.